PENGARUH GREEN ACCOUNTING, KINERJA LINGKUNGAN DAN BIAYA LINGKUNGAN TERHADAP KINERJA KEUANGAN - Budi, Erliana Cahyaning; Zuhrohtun, Zuhrohtun (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.10.TAHUN.2023, 2023)
This study aims to determine the effect of green accounting, environmental performance, and environmental costs on financial performance. The data used in this study are secondary data obtained from annual reports. The population in this study are mining companies listed on the Indonesia Stock Exchange for the 2019-2020 period. The sampling technique in this study used purposive sampling with certain criteria. The sample in this research is 57 samples from 19 companies for 3 years. The data analysis technique used in this study is multiple linear regression analysis. In this study, green accounting was measured using the dummy method, environmental performance was measured using the rating value of the Corporate Performance Rating Program in Environmental Management (PROPER), environmental costs were measured using the environmental development program, and financial performance is measured using return on assets (ROA). The results of the study show that green accounting does not affect financial performance. Environmental performance does not affect financial performance. Meanwhile, environmental costs negatively affect financial performance .